Dual effect of platelet lysate on human articular cartilage : a maintenance of chondrogenic potential and a transient pro-inflammatory activity followed by an inflammation resolution - Pereira, R. C. (2013)
Platelet-rich plasma (PRP), a cocktail of platelet growth factors and bioactive proteins, has been proposed as a therapeutic agent to restore damaged articular cartilage. We report the biological effect of the platelet lysate (PL), a PRP derivative, on primary human articular chondrocytes cultured under both physiological and inflammatory conditions. When added to the culture medium, PL induced a strong mitogenic response in the chondrocytes. The in vitro expanded cell population maintained a chondrogenic redifferentiation potential as revealed by micromass culture in vitro and ectopic cartilage formation in vivo. Further, in chondrocytes cultured in the presence of the proinflammatory cytokine interleukin-1a (IL-1a), the PL induced a drastic enhancement of the synthesis of the cytokines IL-6 and IL-8 and of neutrophil-gelatinase associated lipocalin, a lipocalin expressed during chondrocyte differentiation and inflammation. These events were mediated by the p38 MAP kinase and NF-kB pathways. We observed that inflammatory stimuli activated phospo-MAP kinase-activated protein kinase 2, a direct target of p38. The proinflammatory effect of the PL was a transient phenomenon; after an initial upregulation, we observed significant reduction of the NF-kB activity together with the repression of the inflammatory enzyme cyclooxygenase-2. Moreover, the medium of chondrocytes cultured in the simultaneous presence of PL and IL-1a, showed a significant enhancement of the chemoattractant activity versus untreated chondrocytes. Our findings support the concept that the platelet products have a direct beneficial effect on articular chondrocytes and could drive in sequence a transient activation and the resolution of the inflammatory process, thus providing a rational for their use as therapeutic agents in cartilage inflammation and damage.